2015
DOI: 10.11604/pamj.2015.20.1.5568
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparesis post cerebral malaria

Abstract: Cerebral malaria is one of the most serious complications in the Plasmodium falciparum infection. In endemic areas, the cerebral malaria interested mainly children. The occurrence in adults is very rare and most interested adult traveling in tropical zones. This case report describes a motor deficit post cerebral malaria in a young adult traveling in malaria endemic area. This complication has been reported especially in children and seems very rare in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 6 publications
10
43
1
Order By: Relevance
“…For example, most of the participants in this study were farmers; this is unlikely in a more urbanized setting. Previous studies [ 9 , 12 ] reported employment as significant factors but we had limited variation in our employment categories because of our study setting. There is also a possibility of bias resulting from variable missingness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, most of the participants in this study were farmers; this is unlikely in a more urbanized setting. Previous studies [ 9 , 12 ] reported employment as significant factors but we had limited variation in our employment categories because of our study setting. There is also a possibility of bias resulting from variable missingness.…”
Section: Discussionmentioning
confidence: 99%
“…In Central Africa, it was reported that the HBV prevalence was 4% [ 11 ]. HBV prevalence among women of reproductive age in Nigeria varies depending on the context of study settings, ranging from 7–12% in studies conducted across the country [ 12 18 ]. Overall, there is a paucity of HBV prevalence studies among women of reproductive age in West Africa, and inconsistent HBV prevalence reports in Nigerian studies.…”
Section: Introductionmentioning
confidence: 99%
“…Personal Preference was the fore-most reason for career-selection. Eleven out of 18 participants either have a passion for ObGyn or for surgery, 6 ( Table-I , comment 1-4) while few liked the diversity of having medical and surgical component in ObGyn (Tabl-I, comment 4, 20). 7 This attitude towards surgery is highly motivational, most of our participants enjoy hand-on surgeries and found experiential learning highly effective.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 In adults, the spectrum of presentation includes: psychosis (4%), cerebellar ataxia (3%), extrapyramidal rigidity or hemiplegia. 40 The depth, duration of the coma and multiple seizures were factors for their development. 6 Cognitive difficulties, language and behavior problems have been documented in 24% of children after CM.…”
Section: Prognosticmentioning
confidence: 99%
“…The prevalence of these alterations in adults is not known. 6 Of the clinical spectrum, psychosis is the most common sequel described, also highlighting: 40 hemiplegia, cerebral palsy, blindness and cortical deafness, impairment of cognition and learning. 6,14 Among the rarest manifestations are cases of Gullain-Barre syndrome, cerebellar ataxia, extrapyramidal symptoms, trismus, peripheral neuropathy, isolated and cranial nerve palsy, nystagmus (vertical and horizontal), blindness due to vitreous hemorrhage and encephalomyelitis.…”
Section: Prognosticmentioning
confidence: 99%